Comparative study of the characterisation and extraction techniques of polyphenolic compounds from Acacia seyal gum - Elnour, Ahmed A.M.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen A.; Musa, Khalid Hamid; Shahabipour, Fahimeh; Ashammakhi, Nureddin; Abdurahman, Nour Hamid (Oxford University Press, 2022)
Background: Acacia seyal gum (ASG) is an abundant source of natural polyphenolic compounds (NPPCs) and antioxidant activity with numerous benefits and is often used in cancer treatment. The type of extraction technique can significantly impact the yield and isolation of NPPCs from ASG. The traditional use of maceration extraction reportedly yields fewer NPPCs. Objectives: This study investigated five extraction techniques for NPPCs and ASG antioxidant activity, namely: homogenisation, shaking, ultrasonication, magnetic stirring, and maceration. Materials and methods: The evaluation of the antioxidant activity (AoA) of the extracted NPPCs from ASG used five assays, namely: total flavonoids content, Folin-Ciocalteu index, 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity, ferric reducing antioxidant power, and cupric reducing antioxidant capacity. Results: To minimise the data set dimensionality requires principal component analysis. The ultrasonic and maceration techniques were the best techniques to extract NPPCs and examine the AoA of ASG, with a high correlation between the NPPCs and AoA. However, the maceration process was slow (12 h) compared to ultrasonication (1 h). Slow extraction can result in a decline of the NPPCs due to polyphenol oxidase-enzyme and impact productivity. Conclusions: These findings provide an essential guide for the choice of extraction techniques for the effective extraction of NPPCs from ASG and other plant materials.